The use of whey and other milk by-products in weaned piglet diets - Roxas, D. B. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2004)
This experiment, consisting of two feeding trials, was conducted to assess the use of milk by-products in weaned pig diets. Sixty (60) newly weaned piglets at 30 d, with mean live weight of 8 kg, were randomly allotted to one of six treatment diets, with litters serving as blocks, and ten pigs per treatment, in a randomized complete block design. The treatments were: 1) skimmilk powder (SKM), 2) skimmilk replacer (SMR), 3) lactose (LAC), 4) 15% whey powder (WH15), 5) 25% whey (WH25) and 6) 35% whey (WH35). All the treatments had 3200 kcal ME/kg and 20% CP. In the stage 1 feeding trial, the pigs were fed the treatment diets until they weighed 20 kg. In the stage 2 trial, five of the pigs from each stage 1 treatment were fed a grower diet (3000 kcal ME/kg, 17% CP) without whey powder. The other five pigs received a diet with 5% whey powder. Stage 2 diets were given to the pigs until they weighed 40 kg. In stage 1, pigs fed WH25 had better (P<.05) feed conversion efficiency (FCE) than those fed WH35, WH15, LAC and SKM. Pigs fed SMR had the lowest (P<.05) FCE. However, average daily feed intake (ADFI) and average daily live weight gain (ADG) did not differ among the treatments. The cumulative growth performance of pigs after the stage 2 feeding showed that the highest (P<.05) ADG was that of pigs given WH35 during stage 1, white the lowest (P<.05) was that of pigs given SMR. The cumulative FCE and ADFI values did not differ significantly. The growth parameters were not affected by addition of 5% whey powder during stage 2, indicating that the pig's lactase activity was already low at that stage. Feed cost efficiency evaluation of the diets indicated that providing piglets with high amounts of milk by-products, especially whey, is expected to give favorable results both in feed conversion efficiency and feed cost efficiency of finished or fattened pigs.